Simulasi Pengoperasian Motor Pompa Air Berbasis Programmable Logic Control - Nasution, Elvy Sahnur; Fitra, M; Suhendra, Suhendra; Hasibuan, Arnawan (Politeknik ATI Padang, 2020)
Maintain the availability of clean water in a multy-storey building make the water pump motor oprate continuously which can cause motor damage quickly, because there is no replacement system change of operation of the clean water pump motor conventional outomatic control. PLC (Programmable Logic Control) type Schneider Smart Relay Zelio Logic can be an opration to overcome clean water pump motor operation system to replace convensional automated system in to PLCbased automated systems. Simulation of the operational of a clean water pump motor in a multi-storey build use PLC software type Schneider Zelio Soft2 type SR2B121BD operate 3 clean water pump motors alternately between the source pump motor and the transfer pump motor, measurement of operating time transfer pump motor 1 with transfer pump motor 2 and the design of the alarm system trip to avoid damage to the motor using alarm rirens. Operating of PLC-based automatic water pump motor very helpful oprator to operate the clean water pump motorized, where the operation of a clean water pump motor can be changed trough software as needed.